Study of small signal stability using PSAT including DFIG based wind penetration - Pandey, Ram Prasad (Journal of Innovations in Engineering Education, 2019)
In early days of power engineering, the power system consisting of synchronous generators faced different low frequency oscillation problems and they were solved by different researchers by using suitably AVR and PSS. Later, the electricity industry is turning increasingly to renewable sources of energy to generate electricity. Wind is the fastest growing and the most widely utilized emerging renewable energy technology for power generation at present. With the increasing penetration of wind power in the power system, the impact in power system performance should be fully investigated, particularly for doubly fed induction generation (DFIG) wind turbine since this type of renewable source is gaining prominence in the power system industry. Main purpose of this study is to examine the impacts of wind power integration in the low grid from low frequency oscillation perspective. The benchmarked Two Area System is considered for this analysis using Power System Analysis Toolbox (PSAT). The critical modes of oscillation are selected from eigenvalue analysis and their participation factors are studied to identify their sensitivity. Also the time domain analysis is run in every cases to study the transient stability. From TAS, concept of local and global mode oscillation can be understood clearly. Replacing synchronous generators in TAS by DFIG WTG one by one of same rating gave conclusion that low frequency stability depends on the location of DFIG penetration and operating scenario. The results show that there is both beneficial and detrimental effects due to DFIG WTGs. The installation of PSS in the critical generators greatly enhances the system damping.